A rare case report of metastasis to duraplasty site in a patient with esophageal carcinoma - Ajaya Kumar Ayyappan Unnithan; Anu Jose Markose (Brain Disorders)
A 76-year old man presented with dysphagia, decreased response and generalised weakness. He had acute subdural hematoma two years back and decompressive craniectomy was done for that. After one year, he had poorly differentiated carcinoma of esophagus with multiple metastases in right supraclavicular lymph node, lung, liver, and left ilium. The stage was T3N1M1 and grade was G3. Contrast enhanced computed tomography brain showed an enhancing extraaxial swelling in the craniectomy site, compressing the brain. He went into coma. He was ventilated. Surgical decompression was done. Fleshy pink growth in the plane of duraplasty was excised. He developed myocardial infarction and succumbed. Histopathological result came as metastasis form adenocarcinoma. Immunohistochemistry showed strong membrane positivity for Pan-cytokeratin. This is the first report of a metastasis in duraplasty done for an earlier surgery, although there are lots of reports of metastases in duramater.